Regulation of choroidal blood flow during isometric exercise at different levels of intraocular pressure - Popa-Cherecheanu, Alina (2019)
Purpose: There is evidence that choroidal blood flow (ChBF) is regulated in a complex way during changes in ocular perfusion pressure (OPP). We hypothesized that ChBF regulates better in response to changes in mean arterial pressure (MAP) than in intraocular pressure (IOP). Methods: Eighteen volunteers (mean age, 26 years) were recruited for a randomized, three-way crossover design. MAP was varied via isometric exercise. IOP was either kept normal or elevated by 10 or 20 mm Hg by using a suction cup. Subfoveal ChBF was measured continuously for 8 minutes with laser Doppler flowmetry and OPP was calculated as 2/3*MAP-IOP. For data analysis, values from all subjects were pooled according to either IOP or MAP values, and correlation analyses were done. Results: When data were grouped according to IOP, no correlation was observed between ChBF and MAP, but ChBF was lower the higher the IOP (P < 0.001). When data were grouped according to MAP, a significant correlation was found between ChBF and IOP (P < 0.001). When data were pooled according to IOP, the correlation between ChBF and OPP was weaker (P < 0.05). The OPP at which ChBF significantly increased from baseline was 61.3% ± 4.9% without suction cup, 65.2% ± 3.5% when IOP was increased by 10 mm Hg, and slightly lower when IOP was increased by 20 mm Hg (56.3% ± 4.8%, P = 0.07), but this effect did not reach the level of significance. Conclusions: The present study provides further evidence that the regulation of ChBF during changes in OPP is controlled by complex mechanisms in humans and has less capacity to adapt to IOP elevation than to MAP increase.